Ø£Ø«Ø± Ø§Ù„ØªÙˆØÙŠØ¯ ÙÙŠ Ø§Ù„Ø³Ø¹Ø§Ø¯Ø© Ø¹Ù†Ø¯ Ø§Ø¨Ù† Ù‚ÙŠÙ… Ø§Ù„Ø¬ÙˆØ²ÙŠØ© - Achmad Reza Hutama Al Faruqi; Aqmarina Shofita; Filaila Nur Faiza (IAIN SYEKH NUR JATI, 2021)
Most Muslims used the Western ways to get happiness and did not open their eyes and hearts to a review of ideas about the true happiness in the portrayal of Islam itself and appears in the closure of the Islamic scientific cabinets until it leads to the separation of faith from unification and Happiness. . The study of this research is using the method of Sufism, a kind of Library Research, its purpose is to understand the true meaning of Tauhid and happiness in Ibn Qayyim, and to analyze it in some Muslim scholars, using the descriptive analysis method. The researcher found that Tauhid has the highest place in happiness. Because Tauhid is the belief in God's unity and non-existence. Tawheed is divided into three sections: the Tauhid of rububiyah, the Tauhid of uluhiyah, the Tauhid of Asma wa ash-shifat. The concept of happiness when the son of the values of the nut is the feeling near to God as if he was lying before his Lord, and was the happiness of the son of the values of the nut. And happiness has two types: the earthly happiness and the happiness of the Acharonism. Happiness is divided into three sections: external, physical, and psychological and spiritual happiness heart.